Modeling Expected Years of Schooling Based on Socioeconomic Factors in Banten Province Using the Gamma Regression Model - Oktaviani, Resti (Journal of English Language and Education, 2026)
Despite rapid economic growth in Banten Province, the disparity in Expected Years of Schooling (HLS) between districts/cities remains significant due to socioeconomic factors. This study aims to analyze the effect of Poverty Percentage, Gender Development Index (IPG), and Beneficiary Families (KPM) on HLS using Gamma Regression. A quantitative approach using secondary data from BPS Banten (2020-2024), the population of all districts/cities (n=42 total sampling observations), was analyzed through GLM R Studio with the link log function. The results show that IPG has a significant positive effect on HLS (p=0.007), while Poverty Percentage and KPM have a non-significant negative effect. The model has a high fit (AIC=79.05, MAPE=3.62%, RMSE=0.581) without heteroscedasticity, autocorrelation, or multicollinearity. Gender equality has been shown to be crucial for increasing access to education, although poverty remains a structural barrier.